Educação inclusiva na constituição federal de 1988: uma questão ética e jurídica - Vianna, Carlos Eduardo Souza (2007)
The Brazilian education has the challenge to look for solutions that can answer questions about the access and permanence of the students in its educational institutions, according to the Federal Constitution of 1988. The inclusion of the people in the school atmosphere is related to the principles established in the Federal Constitution of 1988. Citizenship and the dignity of the human being are the foundations our Republic. The Bill pleads as constitutional objectives the promotion of the good of all without preconceptions of origin, race, sex, color, age and any other forms of discrimination. Today the school must be plural. The Educational Institution doesn t evolve when segregating people for possessing different characteristics. These educational spaces cannot continue being places of preconception, discrimination and forgetfulness. The challenge of the modern educator consists to praise the ethical values, starting with respect for all the people, independently of its qualifications and its weaknesses, valuing them as transforming and multiplying beings. The educational institutions, as capable of forming citizens, needs to value and to sow in each classroom the respect for all the people, independently of its peculiarity. Only then, the educational ends proclaimed by the Brazilian Constitution of 1988 will be, in finally, reached